Pengembangan Aplikasi Penjualan Sembako di Toko Sundari Berbasis Desktop - Tukirah, Pamuji Muhamad Jakak; Irawan, Irawan; Uli Riski, Uli Riski; Rahman, Miftakhul (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2024)
The grocery trade sector is one of the vital sectors that provide basic needs for society. Grocery stores play a crucial role in maintaining the availability and accessibility of staple goods for consumers. However, in increasingly tight competition and evolving market demands, grocery stores must update and enhance their operational systems to remain competitive in the dynamic market. In this context, the use of information technology, particularly in the form of desktop-based sales applications, has become an effective solution for improving operational efficiency and customer experience. Such applications enable grocery stores to manage inventory, record sales transactions, and analyze data more efficiently, which in turn can help improve productivity and customer satisfaction. One of the grocery stores focused on in this research is Toko Sundari, which has long been an integral part of the local community. Toko Sundari faces challenges in efficiently managing grocery sales and enhancing customer experience. Therefore, developing a desktop-based grocery sales application at Toko Sundari can benefit the store significantly. The main objective of this research is to create a desktop-based grocery sales application that can assist Toko Sundari in improving operational efficiency, inventory accuracy, and customer experience. Additionally, this research aims to evaluate the implementation of the application at Toko Sundari and analyze its impact on store performance and customer satisfaction. This research utilizes Extreme Programming (XP) methodology as a model for designing the system